New species of the genera Trigonidium Rambur, 1838 and Pteronemobius Jacobson, 1904 from China (Orthoptera: Grylloidea; Trigonidiidae; Trigonidiinae and Nemobiinae) - Yuan, Wei; Zheng, Yan-Na; Ma, Li-Bin; Gu, Jun-Jie (Zootaxa, 2022)
We discovery two new species (Trigonidium nigripes sp. nov. and Pteronemobius luojishanensis sp. nov.) of Trigonidiidae (Orthoptera: Grylloidea) from Sichuan Province, China. T. nigripes sp. nov. is distinct by its tegmen slightly bulging smooth and black, bearing false veins, degraded hindwings and similar wing venation of male and female, and P. luojishanensis sp. nov., is distinguished by its male ectoparamere of genitalia bifurcated and epiphallus relatively short. These species are described and illustrated in this article.